Review on Analytical Method Validation of Nafithromycin - Nishtha Patel; Ayushi Patel; Zarana Pandya; Helly Shah (Asian Journal of Pharmaceutical Research and Development, 2025)
Background: Nafithromycin (synonym WCK-4873), marketed under the brand name Miqnaf, represents India’s first indigenously developed antibiotic targeting drug-resistant infections. Wockhardt Limited developed Nafithromycin with financial and technical support from the Biotechnology Industry Research Assistance Council (BIRAC). The Central Drugs Standard Control Organisation (CDSCO) has approved it for the treatment of community-acquired bacterial pneumonia (CABP).The drug achieves effective lung concentrations and delivers therapeutic out comes with a three-day oral regimen, improving patient compliance while reducing treatment time. Methods: Researchers validated Nafithromycin analytically using three key methods. They employed the RP-HPLC method with a C18 column, anisocratic mobile phase of buffer and acetonitrile (60:40), and UV detection. They applied the RP-UPLC method with a BEHC18 column, a gradient mobile phase of 0.1%formicacidinwaterandacetonitrile, and PDA detection. They used the UHPLC-MS method with a C18 column, an isocratic mobile phase of 0.1% formic acid and acetonitrile (30:70), and mass spectrometry detection. Conclusion: Nafithromycin (Miqnaf) emerges as a reliable, indigenous antibiotic for community-acquired bacterial pneumonia. Analytical validation through RP-HPLC, RP-UPLC, and UHPLC-MS confirms accuracy and robustness. These findings ensure quality, safety, and efficacy, highlighting Nafithromycin’s promise as a short-course therapy against drug-resistant respiratory pathogens and a milestone in antibiotic innovation.